2018
DOI: 10.1002/2017jc013388
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Propagation of Nonlinear Internal Waves in Sheared Currents Over the Washington Continental Shelf

Abstract: The generation, propagation, and dissipation of nonlinear internal waves (NLIW) in sheared background currents is examined using 7 days of shipboard microstructure surveys and two moorings on the continental shelf offshore of Washington state. Surveys near the hypothesized generation region show semi‐diurnal (D2) energy flux is onshore and that the ratio of energy flux to group speed times energy ( F/cgE) increases sharply at the shelf break, suggesting that the incident D2 internal tide is partially reflected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 77 publications
1
9
0
Order By: Relevance
“…The observations documented that trains of NLIWs evolved into waves of elevation during shoaling, which is consistent with previous investigation of continental shelf internal waves from observations, theory and numerical simulation (Vlasenko and Hutter 2002;Grimshaw et al 2004;D'Asaro et al 2007;Shroyer et al 2009;Hamann et al 2018;Jones et al 2020). Yet the spatially continuous DTS observations also showed that the signatures of the wave-trains grew weaker and ultimately disappeared as the waves moved across the inner shelf towards the surfzone (Figs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The observations documented that trains of NLIWs evolved into waves of elevation during shoaling, which is consistent with previous investigation of continental shelf internal waves from observations, theory and numerical simulation (Vlasenko and Hutter 2002;Grimshaw et al 2004;D'Asaro et al 2007;Shroyer et al 2009;Hamann et al 2018;Jones et al 2020). Yet the spatially continuous DTS observations also showed that the signatures of the wave-trains grew weaker and ultimately disappeared as the waves moved across the inner shelf towards the surfzone (Figs.…”
Section: Discussionsupporting
confidence: 91%
“…Subsequently, Sinnett et al (2018) showed that NLIWs of tidal and tidal-harmonic frequencies could be tracked across the mid-and inner shelf, occasionally reaching past the Pier-end into the surf-zone. These waves were described as "bore-like," in analogy to similar wave-forms observed in central California (Walter et al 2014;Spydell et al 2021), the Oregon continental shelf (D'Asaro et al 2007), and elsewhere (Alford et al 2015;Hamann et al 2018). At times, trains of high-frequency (6-10 cph) NLIWs were found to be superimposed over the lower frequency internal tide (e.g.…”
Section: Physical Setting and Observations A Settingmentioning
confidence: 71%
“…In the study, we make the first step to investigate the effect of the background current on the NLIWs by adding a horizontal and vertical uniform background current in the 2D numerical model. The model shows that the current greatly changes the evolution process of internal waves and reduces the occurrence time of SAR-observed NLI-Ws by 4 h. Given the strong horizontal and vertical shear of background currents, a field measurement (Hamann et al, 2018) is necessary in the future to clarify how the current shear affects the generation and evolution of internal waves.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past four decades, a number of studies have focused on quantifying the mixing induced by IWs (Jones et al, 2020;Lamb, 2014;MacKinnon et al, 2017;Moum et al, 2003;Palmer et al, 2015;Sandstrom and Oakey, 1995;Vic et al, 2019). However, the complex interactions of internal waves with topography mean that understanding the energy dissipation processes and quantifying IW mixing rates on the continental shelf is not an easy task and remains an active area of research (Grados et al, 2016;Hamann et al, 2018;Nash et al, 2012;Zulberti et al, 2020). As pointed out by Schafstall et al (2010), a general parameterization of mixing for such areas is still lacking.…”
Section: Internal Waves and Diapycnal Mixing In The Coastal Oceanmentioning
confidence: 99%